2010
DOI: 10.1590/s0100-204x2010000800009
|View full text |Cite
|
Sign up to set email alerts
|

Componentes de la variabilidad espacial en el manejo por sitio específico en banano

Abstract: Resumen -El objetivo de este trabajo fue evaluar la variabilidad espacial de la producción de banano en función de variables físicas y químicas del suelo y de las características fisiográficas de la finca, con miras a seleccionar aquellas con mayor potencial de uso en programas de manejo por sitio específico. Se georreferenciaron 130 unidades productivas de banano clon Williams (Cavendish AAA) distribuidas en cuatro lotes de la finca y tres unidades de suelo. Se determinó el peso del racimo y la cantidad de ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…Nowadays there is a great interest from banana farmers in Venezuela, among other producing countries, to optimize input use in plantations. For this, characterizing the productive efficiency of banana plots will facilitate the delimitation of zones for differentiated management (Castañeda et al 2010). This study identified the soil properties most associated with banana productivity in two producing areas if Venezuela to explore the potential development of empirical simple models that could help in predicting the banana productivity by estimating a PI as a function of soil characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays there is a great interest from banana farmers in Venezuela, among other producing countries, to optimize input use in plantations. For this, characterizing the productive efficiency of banana plots will facilitate the delimitation of zones for differentiated management (Castañeda et al 2010). This study identified the soil properties most associated with banana productivity in two producing areas if Venezuela to explore the potential development of empirical simple models that could help in predicting the banana productivity by estimating a PI as a function of soil characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, banana at high soil compaction presents a significant decrease in the total number of leaves, the average leaf area, the total leaf area, the diameter of the pseudo stem, and the height of the succession plant (Villarreal-Núñez et al 2013). Drastic changes in soil aggregation, in the presence of expandable clays, or soil compaction associated with less porosity and poor drainage, could damage roots and affects banana production (Araya and Blanco 2001;Castañeda et al 2010). Textural extremes (clay and sand) are also factors that limit the growth of the banana root (Aguirre et al 2012).…”
Section: Discussionmentioning
confidence: 99%